Attachment of human C5a des Arg to its cochemotaxin is required for maximum expression of chemotactic activity. - Perez, H D (1986)
The chemotactic activity of human C5a des Arg is enhanced significantly by an anionic polypeptide (cochemotaxin) in normal human serum and plasma. We have found that the cochemotaxin attaches to the oligosaccharide chain of native C5a des Arg to form a complex with potent chemotactic activity for human polymorphonuclear leukocytes. Although capable of enhancing the chemotactic activity of native C5a des Arg, the cochemotaxin had no effect on the chemotactic activity of either deglycosylated C5a des Arg, native C5a, or N-formyl-methionyl-leucyl-phenylalanine. Of the known components of the oligosaccharide chain, only sialic acid prevented enhancement by the cochemotaxin of the chemotactic activity exhibited by native C5a des Arg. Sialic acid also prevented the formation of C5a des Arg-cochemotaxin complexes, detected by acid polyacrylamide gel electrophoresis, molecular sieve chromatography on polyacrylamide gels, and sucrose density gradient ultracentrifugation.